Corporate Social Responsibility Performance and Money Laundering Control Systems: Evidence from Australian Financial Institutions - Jiang, Lu (Curtin University, 2020)
This study investigates the relationship between money laundering control systems (MLC) and corporate social responsibility performance (CSRP). The moderating effects of use of correspondent banking and tax havens on that relationship are additionally examined. Based on a dataset of 625 firm-year observations comprising publicly-listed Australian financial institutions over the 2008–2017 period, a positive and significant relation between firms’ corporate social responsibility performance and the strength of money laundering control systems is observed.